Effect of silicon fertilization and crop establishment methods on yield, soil quality and silicon uptake of rice (Oryza sativa) - BAJIYA, ROHITASH; SINGH, Y V; SHARMA, D K; DASS, ANCHAL; MEENA, M C; ABRAHAM, G; BANA, R S; LAKHRAN, HANSA (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was carried out at ICAR-Indian Agricultural Research Institute, New Delhi during kharif 2015 and 2016 to determine the effects of rice establishment method, silicon application levels and silicon solubilizing bacteria on silicon concentrations and uptake by rice (Oryza sativa) and soil microbial parameters in rice-wheat cropping system. The experiment was laid out in split-split plot design and replicated thrice. The experiment was conducted with 24 treatment combinations including rice establishment methods in main plot, silicon level in sub plot and silicon solubilizing microbes in sub-sub plot. Silicon concentration in grain and straw was highest in crop establishment of aerobic rice and lowest in TPR methods during both the years. Tested aerobic rice establishment methods significantly influenced the microbial biomass carbon (278.2 and 289.3 μg/g soil), soil dehydrogenase activity (202.3 and 198.3 μg TPF/g soil/day) and total count of silicon solubilizing bacteria (222.5 and 255.9 × 102 cfu/g soil) compared to SRI and TPR and the highest silicon concentration and uptake, microbial biomass carbon (285.9 μg/g soil), dehydrogenase activity (189.7 μg TPF/g soil/day) and total count of silicon solubilizing bacteria (239.6 102 cfu/g soil) was recorded with silicon application 120 kg/ha which at par with 80 kg/ha but statistically superior over to control and 40 kg/ha in terms of nutrient uptake in grain and straw and soil quality parameters during both years of study.